Development of virtual lab-assisted guided inquiry teaching materials to improve science literacy on momentum and impulse material - Fitriana, Sheila; Riska, Fati Matur; Decenni Amelia; Rachmat Rizaldi; Syahwin; Tri Astuti Mardiana (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
The development of science and technology in the 21st century necessitates strong scientific literacy among students, yet Indonesian students' PISA scores in this area remain low. Conventional physics teaching materials often lack interactivity and fail to engage students actively, especially for abstract topics like momentum and impulse. This research addresses the gap by developing guided inquiry-based teaching materials assisted by virtual laboratories (V-Lab) for momentum and impulse, aiming to improve senior high school students' scientific literacy. The study employed a Research and Development (R&D) method focusing on the define, design, and develop stages. Module feasibility was assessed through validation by material and media experts using questionnaires (1-4 Likert scale), yielding quantitative scores and qualitative feedback. Initial field testing involved 32 10th-grade students and utilized readability questionnaires, learning interest questionnaires, and pre-post science literacy tests, analyzed descriptively. Results showed high feasibility: material expert validation at 91.6% (Very Good) and media expert validation at 84.0% (Very Good). Qualitative feedback affirmed the module's strengths and provided suggestions for refinement. Initial field testing indicated very good student readability (86.3%) and learning interest (82.0%). Science literacy improved from a pre-test average of 45.2% to a post-test average of 75.8%, with a Normalized Gain (N-Gain) of 0.56 (Medium effectiveness). The study concludes that the developed V-Lab assisted guided inquiry teaching materials are highly feasible and effective for enhancing students' science literacy. The module offers a valuable, interactive resource for physics education, with potential for wider application